Service Quality dan Importance Performance Analysis Program Studi Manajemen Universitas Flores - Yulius Laga (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2019)
This study adopts a service quality approach and importance performance analysis (IPA) applied to tertiary institutions, to analyze how big the role of service in tertiary institutions (lecturers and employees) is towards students who in certain contexts are valued as consumers. This research was conducted at the University of Flores management study program, with 50 samples (stratified random sampling). Test the suitability and accuracy of the data by conducting validity and reliability tests, data analysis using the SERVQUAL and IPA methods by assessing physical evidence, reliability, responsiveness, assurance, empathy on the basis of GAP value considerations and priority plots using Cartesian Diagrams. The results showed the Management study program needs to improve service priority (GAP) whose value exceeds -0.5 and low priority value in the plot diagram.